Pengaruh Hedonic Shopping Motives dan Promosi Penjualan Terhadap Impulsive Buying: Studi pada Konsumen Gudang Kosmetik Purwokerto - Dinda Puspa Salsabilla; Restu Frida Utami; Arini Hidayah; Alfato Yusnar Kharismasyah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The increasingly rapid and stringent development of the cosmetics industry requires companies to continue improving their strategies and innovations to survive and compete. This research analyzes the influence of hedonic shopping motives and sales promotions on impulsive buying. This type of research is quantitative research. The number of samples in this study was 106 respondents taken based on purposive sampling techniques. Data analysis in this study used multiple linear regression analysis with the help of SPSS software version 26.00. The research results showed that 1) hedonic shopping motives have a positive and significant effect on impulsive buying, 2) sales promotions have a positive and significant effect on impulsive buying, 3) There are no differences in impulse buying behavior based on employment status.